MANAJEMEN ASKEP DALAM PENERAPAN SLOW STROKE BACK MASSAGE UNTUK PENINGKATAN KUALITAS TIDUR PADA PENDERITA HIPERTENSI DI PUSKESMAS PAMPANG - Siti Zohra Lastuan; Andi Mappanganro; Tutik Agustini; Rizky Iftitah Alam (CV. Adiba Aisha Amira, 2025)
Hypertension is a chronic disease that can cause complications, including sleep disorders. Sleep disorders in patients with hypertension can reduce quality of life and increase the risk of cardiovascular complications. Slow stroke back massage nonpharmacological therapy is one intervention that can be used to improve sleep quality. This case report aims to describe the application of slow stroke back massage on the sleep quality of patients with hypertension at the Pampang Community Health Center. The method used was nursing care, which included assessment, data analysis, diagnosis, planning, implementation, and evaluation. Hypertensive patients experienced difficulty sleeping, frequent nighttime awakenings, headaches, and tension in the neck and back. The intervention, which consisted of sleep support and pain management with slow stroke back massage, was carried out for three days with a duration of 10–15 minutes per session. The evaluation results showed a decrease in sleep difficulties, a reduction in the frequency of waking up at night, a decrease in pain intensity, and an increase in patient sleep satisfaction. The conclusion of this report is that slow stroke back massage is effective as a non-pharmacological therapy to improve sleep quality in hypertensive patients.